Accurate unsupervised monocular depth estimation for ill-posed region - Wang, Xiaofeng; Sun, Jiameng; Qin, Hao; Yuan, Yuxing; Yu, Jun; Su, Yingying; Sun, Zhiheng (Frontiers in Physics, 2023)
Unsupervised monocular depth estimation is challenging in ill-posed regions, such as weak texture scenes, projection occlusion, and redundant error of detail information, etc. In this paper, in order to tackle these problems, an improved unsupervised monocular depth estimation method for the ill-posed region is proposed through cascading training depth estimation network and pose estimation network by loss function. Firstly, for the depth estimation network, a feature extraction network using asymmetric convolution is designed instead of traditional convolution, which strengthens the extraction of the feature information and improves the accuracy of the weak texture scenes. Meanwhile, a feature extraction network integrating multi-scale receptive fields with the structure of different scale convolution and dilated convolution stack is designed to increase the underlying receptive field of the depth estimation network, which strengthens the fusion ability of the network for multi-scale detail information, and improves the integrity of the model output details. Secondly, a pose estimation network using an attention mechanism is presented to strengthen the pose detail information of keyframes and suppress redundant errors of the pose information of non-keyframes. Finally, a loss function with minimum reprojection error is adopted to alleviate the occlusion problem of the projection process between adjacent pixels and enhance the quality of the output depth images of the model. The experiments demonstrate that our method achieves state-of-the-art performance on KITTI monocular datasets.